1994
DOI: 10.1104/pp.105.3.965
|View full text |Cite
|
Sign up to set email alerts
|

Endo-1,4-[beta]-Glucanase, Xyloglucanase, and Xyloglucan Endo-Transglycosylase Activities Versus Potential Substrates in Ripening Tomatoes

Abstract: In ripening fruits of tomato (Lycopersicon esdentum 1. var 83-C-38), the amounts of cellulose and xyloglucan (XC) remained constant during tissue softening, but the relative molecular weight (M,) of XG decreased markedly and the M, of cellulose declined slightly. These changes could have been due to adivities of nonspecific endo-1,4-@-glucanases and/or buffer-soluble XC endotransglycosylase, both of which increased when tissue firmness declined most rapidly. Tomato extracts also reduced the viscosity of XC sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
107
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(112 citation statements)
references
References 28 publications
5
107
0
Order By: Relevance
“…In sycamore suspension-cultured cells, half of the XG polymer is composed of the subunits XXFG and XXXG; however, the rest of the molecules is composed of subunits with more extensive sidechain substitution (York etal., 1995). In another example, XG from the growing tissues of tobacco and tomato does not possess subunits with fucosylated trisaccharide sidechains (Maclachlan and Brady, 1994;Seymour et aL, 1990;York et aL, 1996). However, it appears that the sidechain chemistry in these XGs is appreciably different from the forms discussed in this study (York et aL, 1996) and it is therefore possible that different conformational preferences dictate the formation of the cellulose binding conformation.…”
Section: Mechanisms Of Xg Binding To Cellulosementioning
confidence: 65%
“…In sycamore suspension-cultured cells, half of the XG polymer is composed of the subunits XXFG and XXXG; however, the rest of the molecules is composed of subunits with more extensive sidechain substitution (York etal., 1995). In another example, XG from the growing tissues of tobacco and tomato does not possess subunits with fucosylated trisaccharide sidechains (Maclachlan and Brady, 1994;Seymour et aL, 1990;York et aL, 1996). However, it appears that the sidechain chemistry in these XGs is appreciably different from the forms discussed in this study (York et aL, 1996) and it is therefore possible that different conformational preferences dictate the formation of the cellulose binding conformation.…”
Section: Mechanisms Of Xg Binding To Cellulosementioning
confidence: 65%
“…Tomato fruit ripening includes the progressive and extensive loss of firmness that is largely a result of metabolism of the cell wall polysaccharides (Brummell, 2006;Cantu et al, 2007Cantu et al, , 2008a. The ripeningassociated disassembly of hemicellulosic and pectic cell wall polysaccharides is known to be severely reduced in rin fruit and apparently is diminished in nor and 1-MCP-treated fruit, since they also have only limited softening (Seymour et al, 1987;Giovannoni et al, 1989;DellaPenna et al, 1990;Maclachlan and Brady, 1994). We have previously shown that fruit susceptibility to B. cinerea depends on LePG and LeExp1, two proteins that participate in the disassembly of the cell wall, which are expressed in ripe fruit even though B. cinerea secretes its own polysaccharidehydrolyzing enzymes (van Kan, 2006;Cantu et al, 2008a).…”
Section: Discussionmentioning
confidence: 99%
“…[In ripening fruits of tomato (Lycopersicon esculentum L. var 83-G-38), the amounts of cellulose and xyloglucan remained constant during tissue softening, but the relative molecular weight of xyloglucan decreased markedly and the Mr of cellulose declined slightly] (Maclachlan and Brady, 1994). Xyloglucan is the principal hemicellulose and present in both dicot and monocot cell walls, although it is present in far larger amounts in the walls of dicots (about 20 %) relative to those of monocots (about 2 %) (Darvill et al, 1980).…”
Section: Cell Wall Structure and Softening -Associated Changesmentioning
confidence: 99%